CONSTITUENTS OF ESSENTIAL OILS OF SOME AROMATIC PLANTS AND THEIR EFFECT ON OXIDATIVE STABILITY OF SUNFLOWER OIL - Omar Fawzi Abdulaziz (Mesopotamia Journal of Agriculture)
The constituents of hydrodistilled essential oils from wild Mentha longofolia L. and Thymbra spicata L. grow in Mosul and Duhok regions of Northern Iraq while Salvia officinalis L. and Rosmarinus officinalis L. were imported from Syria. The study showed that the major components of the essential oils mentioned above, were carvone (26.47%), carvacrol (67.65%), 1,8-cineole (55.68%) and 1,8-cineole (53.86%) respectively.Further the study showed that the addition of 1000mg/kg of Rosmarinus officinalis L. and Thymbra spicata L. oils had a positive effect while the addition of same ratio of Mentha longifolia L. and Salvia officinalis L. oils gave a negative effect on oxidative stability of Sunflower oil .